2014
DOI: 10.1186/1750-1326-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar protein sorting 35 (Vps35) rescues locomotor deficits and shortened lifespan in Drosophila expressing a Parkinson’s disease mutant of Leucine-rich repeat kinase 2 (LRRK2)

Abstract: BackgroundParkinson’s disease (PD) is the most common movement neurodegenerative movement disorder. An incomplete understanding of the molecular pathways involved in its pathogenesis impedes the development of effective disease-modifying treatments. To address this gap, we have previously generated a Drosophila model of PD that overexpresses PD pathogenic mutant form of the second most common causative gene of PD, Leucine-Rich Repeat Kinase 2 (LRRK2).FindingsWe employed this model in a genetic modifier screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 58 publications
(59 reference statements)
4
85
0
Order By: Relevance
“…Second, in all cases, the disease is caused by a loss rather than a gain of retromer function. This agrees with observations in yeast, neuronal culture, and animal models that have shown that, whereas a slight loss of retromer function has dramatic pathological consequences, increasing retromer levels seems to be either beneficial or innocuous [40]. This speaks to the concern that increasing retromer levels in many cells, be it genetically or pharmacologically, might have negative side effects.…”
Section: Retromer In Other Diseasessupporting
confidence: 90%
“…Second, in all cases, the disease is caused by a loss rather than a gain of retromer function. This agrees with observations in yeast, neuronal culture, and animal models that have shown that, whereas a slight loss of retromer function has dramatic pathological consequences, increasing retromer levels seems to be either beneficial or innocuous [40]. This speaks to the concern that increasing retromer levels in many cells, be it genetically or pharmacologically, might have negative side effects.…”
Section: Retromer In Other Diseasessupporting
confidence: 90%
“…The pathogenic mutations, G2019S , R1441C and Y1699C enhanced Golgi clearance, but the hypothesis‐testing mutations that decrease GTP binding, the T1348N, or the kinase‐inactive K1906M, did not sustain Golgi clearance, suggesting that both kinase and GTPase activities are required for maintaining this cellular process 118. Overexpression of VPS35 exhibited protective effects in mutant LRRK2 Drosophila 132; it is of interest to note that mutations in the VPS35 encoding gene have been identified in PD families 133, 134, further implicating the disruption of retromer mediated protein sorting as potentially leading to PD.…”
Section: Lrrk2 Function In Vesicle Dynamics and Retromer Functionmentioning
confidence: 99%
“…While within the last half decade we considerably learned about the genetics of VPS35 patients, we have nothing at hand to offer our clinical VPS35 patients. More human case reports including neuropathology would be needed to find a specific clinical marker of VPS35 patients to allow a targeted referral to genetic testing [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%